Collaborative computing : networking, applications and worksharing : 13th International Conference, CollaborateCom 2017, Edinburgh, UK, December 11-13, 2017, Proceedings /: networking, applications and worksharing : 13th International Conference, CollaborateCom 2017, Edinburgh, UK, December 11-13, 2017, Proceedings. (2018) - Unknown
No abstract available